Remediating cognitive inflexibility in obsessive compulsive disorder and anorexia nervosa neither moderates nor mediates treatment effects: an exploratory study - van Passel, Boris; Danner, Unna N.; Dingemans, Alexandra E.; Broekman, Theo G.; Sternheim, Lot C.; Becker, Eni S.; van Elburg, Annemarie A.; van Furth, Eric F.; Hendriks, Gert-Jan; Cath, Daniëlle C. (Frontiers in Psychiatry, 2025)
ObjectiveObsessive compulsive disorder (OCD) and anorexia nervosa (AN) are conditions associated with poor cognitive flexibility, a factor considered to interfere with treatment, but research into the relationship between cognitive flexibility and treatment outcome is limited. This study explores whether baseline measures of cognitive flexibility predict outcomes in OCD and AN, evaluates whether changes in these measures contribute to treatment outcome, and evaluates the effectiveness of adjunctive cognitive remediation therapy (CRT) in improving cognitive flexibility.MethodsThis secondary analysis utilized linear mixed model analysis on data from a randomized controlled multicenter clinical trial involving adult participants with OCD (n=71) AND AN (n=61). Participants underwent 10 twice-weekly sessions of either CRT or a non-specific active control intervention (specialized attention therapy; SAT), followed by treatment as usual. Assessments using Yale-Brown Obsessive Compulsive Scale and the Eating Disorder Examination Questionnaire were conducted at baseline, post-CRT/SAT and at 6 and 12 months. Cognitive flexibility was evaluated through the Trail Making Test (TMT), the Color-Word Interference Test (CWIT) and the Detail and Flexibility Questionnaire (DFlex).ResultsLevels of cognitive flexibility at baseline did not predict or moderate treatment outcome, nor did change in cognitive flexibility (baseline post-CRT/SAT) mediate treatment outcome, with CRT providing no greater improvement in measures of cognitive flexibility than SAT.ConclusionsThis study failed to find any relationship between measures of cognitive flexibility and treatment outcome in OCD and AN, and thus questions hypothetical associations between measures of cognitive flexibility and mechanisms of change in patients with OCD and AN.